A protective role of IL-37 in cancer: a new hope for cancer patients. Issue 2 (23rd November 2016) - Abulkhir, Ayoub; Samarani, Suzanne; Amre, Devendra; Duval, Michel; Haddad, Elie; Sinnett, Daniel; Leclerc, Jean-Marie; Diorio, Caroline; Ahmad, Ali
Abstract: IL-37 is a cytokine belonging to the IL-1 family. Although discovered in silico in 2000, significant advances in the understanding of its biology were made only in recent years. It is a member of the family with potent anti-inflammatory and immunosuppressive properties. It is produced as a precursor without a classic signal peptide. The precursor is cleaved into mature form in the cytoplasm by caspase-1. A small fraction of the cleaved IL-37 binds SMAD-3, translocates to the nucleus, and suppresses transcription of several proinflammatory genes. Both precursor and cleaved forms of IL-37 are secreted. They bind IL-18Rα chain (also used by IL-18 as a receptor subunit) and recruit Toll/IL-1R (TIR)-8 for transducing intracellular signaling. TIR-8 is a member of the IL-1 receptor family (IL-1RF) and was previously known as an orphan receptor. IL-37 suppresses activation of NF-κB and MAPK and activates Mer–PTEN-DOK pathway. It negatively regulates signaling mediated by TLR agonists, proinflammatory cytokines, and IL-1RF ligands. It also affects cell metabolism by inhibiting mTOR, GSK-3α/β, and activating AMPK. Despite having the ability to dampen host's immune responses, the cytokine has been shown to exert antitumor effects, and it has been suggested that it may act as a prognostic marker in a variety of human cancers. Recent studies have suggested that IL-37 may represent a novel therapeutic tool in patients with cancer. In this review, we provide an overview of the cytokine biology, discuss recent advances made in unraveling its anti-cancer effects, and suggest guidelines for future research.